(untitled) (Third Sector Social Economic Review, 2024)
The aim of this study is to determine the effectiveness of indicators of Government Domestic Debt Securities in the investment decisions for those who invest in Government Domestic Debt Securities traded on world stock exchanges. For this purpose, 8 indicators were used in the study with the help of annual data obtained from the official website of the World Federation of Exchanges from 2015 to 2022. These indicators; Value of Government Debt Securities, number of issuers of Government Debt Securities, number of Government Debt Securities, number of new Government Debt Securities, total value of Government Debt Securities trade, State traded through electronic order book The value of Government Debt Securities is the value of Government Debt Securities traded through a negotiated agreement and the value of investment flows - the value of new capital growing with Government Debt Securities). This study, in which the order of importance of the indicators regarding the LOgarithmic Percentage Change-driven Objective Weighting method, one of the multi-criteria decision-making methods, is determined, is the first study in which the multi-criteria decision-making method is used in the literature on Government Debt Securities and the first study to use the LOgarithmic Percentage Change-driven Objective Weighting method. It is original because it was made on a subject related to State Government Debt Securities.